(untitled) (Research, Society and Development, 2026)
Introduction: Childhood obesity has increased globally and is a serious public health problem. In Brazil, the nutritional transition has led to an increase in overweight, with contributing factors. This condition can cause metabolic and cardiovascular diseases, social impacts, and higher healthcare costs. Preventing it requires a multidisciplinary approach and family involvement. This article aims to review the literature to support the creation of an educational video on the prevention and non-pharmacological treatment of childhood obesity. Methodology: This study is a literature review on the prevention of childhood obesity. Results and discussion: Prevention involves multicomponent approaches, including changes in nutrition, behavior (sleep and screen time), and physical activity. School-based interventions, combined with family participation, are effective, especially through teacher training and parental involvement in promoting healthy food and exercise choices. Nutrition education in schools is also important. Conclusion: Preventing childhood obesity requires an integrated approach involving family, school, and healthcare, combining improvements in diet, physical activity, sleep, and screen time. Collaboration among these sectors is essential, although socioeconomic barriers and parental misconceptions remain challenges.